Wound infection in non-perforated acute appendicitis- single dose preoperative antibiotics vs. prophylactic postoperative antibiotics: does it make any difference? - Shirah, Bader Hamza; Shirah, Hamza Asaad (International Journal of Research in Medical Sciences, 2016)
Background: Antibiotics are used pre and postoperatively in acute appendicitis for preventing wound infection. Recent studies showed that the use of postoperative antibiotics is not necessary in cases of non-perforated appendicitis as only prophylactic antibiotics are sufficient. Therefore, we aim in this study to evaluate the outcome of two protocols of wound infection prophylaxis in non-perforated appendicitis with single dose preoperative antibiotics only compared to pre and postoperative antibiotics. Methods: 482 Saudi Arabian patients treated surgically for acute appendicitis between January 2010 and December 2014 were reviewed. Inclusion criteria included adult patients diagnosed initially as acute appendicitis. Patients proven to have had perforated appendix were excluded. Results: 482 patients, 213 (44.2%) male and 269 (55.8%) female were included. The mean age was 26.21±6.123 years. Mean hospital stay was 2.17 ± 0.81. In group 1 (only preoperative antibiotics) the total number of patients was 237 (49.7%), in which 17 (3.5%) developed wound infection. In group 2 (pre and postoperative antibiotics), the total number of patients was 245 (50.8%), in which 20 (4.1%) developed wound infection. The overall wound infection rate was 7.6 % (37 patients out of 482). No significant difference between both groups in regard to wound infection was found, (p = 0.9182). Conclusions: Patients undergoing operation for non-perforated appendicitis needed only a single dose of preoperative antibiotics to prevent postoperative wound infection. Continuing antibiotic prophylaxis in the postoperative period did not add an appreciable clinical benefit in these patients.